Book review: Our Senses: Gateways to Consciousness, written by Rob DeSalle - Spence, C (Brill, 2018)
Charles Spence reviews Rob DeSalle’s (2018) new book Our Senses: Gateways to Consciousness, a popular science look at the neuroscience behind the senses set in an evolutionary context.